A Justiça moçambicana e as questões de interpretação forense : um longo caminho a percorrer - Timbane, Alexandre António (Language and Law / Linguagem e Direito, 2017)
Mozambique is a very diverse country sociolinguistically. The language of justice, Portuguese, is not known to most Mozambicans but the police use it in legal documents. Hence there arises the question: does the Mozambican justice system give any weight to interpreting in forensic contexts? There is certainly a need for interpreters in police interviews to convert not only from Bantu languages into Portuguese, but also from sign language. This article sets out to discuss the relevance of forensic interpreters in interviews, to explain the complexity of the link between language and culture and to reect on the importance of forensic linguistic interpreting. The research concluded that there is a need to train police ocers to interpret and translate because at the moment many case aspects linked to language are omitted by ocials, due to their lack of knowledge of the language of the suspect accused.